Real-World Treatment Patterns in Patients with Vitiligo in the United States - David Rosmarin; Ahmed M. Soliman; Chao Li (Adis, Springer Healthcare, 2023)
Abstract Introduction Vitiligo is an autoimmune disorder resulting in skin depigmentation, with limited approved treatment options. This study evaluated medication utilization and treatment patterns among patients in the first year following vitiligo diagnosis. Methods This retrospective analysis of claims data from the Merative® MarketScan Research Databases included patients aged ≥ 12 years newly diagnosed with vitiligo. Patients were identified between October 1, 2016, and April 30, 2021, and had ≥ 12 months of continuous enrollment pre- and post-vitiligo diagnosis. Medication use, treatment line of therapy, time to and number of medication claims, and length of therapy were reported in the 12 months post-vitiligo diagnosis. Results are reported separately for treatment initiators post-vitiligo diagnosis, patients with moderate-to-severe vitiligo, and adolescents (aged 12-17 years). Results A total of 19,335 patients were included in the analysis, with half (N = 9648, 49.9%) not receiving any treatment during the 12-month follow-up. Switching was minimal among treatment initiators (N = 5845) in the 12 months post-vitiligo diagnosis, with the most frequent first-line treatments being high-potency topical corticosteroids (25.4%), oral corticosteroids (23.1%), and topical calcineurin inhibitors (TCI, 14.7%). Adolescents initiating treatment (N = 486) most frequently received TCI (30.9%) as first-line therapy. Patients with moderate-to-severe vitiligo (N = 3462) were very likely to receive treatment during follow-up, with only 1.5% not receiving treatment. Among patients with no vitiligo treatment prior to diagnosis, time to first medication claim ranged from 51.9 days (standard deviation [SD], 84.0) for TCI to 178.6 days (SD 116.0) for systemic immunosuppressants; mean total days supplied ranged from 14.4 days (SD 27.1) for oral corticosteroids to 121.0 (SD 114.0) for immunosuppressants. Conclusion In this real-world study, a high proportion of patients did not receive any treatment. Among those receiving treatment, most were unlikely to switch or use a combination of treatments within the first year of vitiligo diagnosis.